2023
DOI: 10.3390/ijerph20043686
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Land-Based Approaches to Well-Being: The Niska (Goose) Harvesting Program in Subarctic Ontario, Canada

Abstract: Historically, goose harvesting provided a source of culturally significant, safe, and nutritious food for the Omushkego Cree of subarctic Ontario, Canada. Disruptions stemming from colonization and climate change have led to a decrease in harvesting, resulting in higher rates of food insecurity. The aim of the Niska program was to reconnect Elders and youth to revitalize goose harvesting activities and associated Indigenous knowledge within the community. The program and evaluation were built using a two-eyed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 103 publications
0
19
0
Order By: Relevance
“…Other authors may have identified as Indigenous but not noted it within the article text. Materials and methods (meaningful data collection, research) As data collection instruments, studies employed digital cameras ( n = 22), disposable cameras ( n = 12), or cameras of an unspecified type ( n = 10) for photo‐taking. Other methods included smartphones (Brown, 2016; Holliday et al, 2018; Spiegel et al, 2020), a GPS with camera capabilities (Isogai et al, 2015), GoPros (Ahmed et al, 2022, 2023), or a tablet shared between all participants (Kahn‐John et al, 2020). Six studies did not specify the photo‐taking method used.Nine studies combined other data collection methods with photo‐taking.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors may have identified as Indigenous but not noted it within the article text. Materials and methods (meaningful data collection, research) As data collection instruments, studies employed digital cameras ( n = 22), disposable cameras ( n = 12), or cameras of an unspecified type ( n = 10) for photo‐taking. Other methods included smartphones (Brown, 2016; Holliday et al, 2018; Spiegel et al, 2020), a GPS with camera capabilities (Isogai et al, 2015), GoPros (Ahmed et al, 2022, 2023), or a tablet shared between all participants (Kahn‐John et al, 2020). Six studies did not specify the photo‐taking method used.Nine studies combined other data collection methods with photo‐taking.…”
Section: Resultsmentioning
confidence: 99%
“…As data collection instruments, studies employed digital cameras ( n = 22), disposable cameras ( n = 12), or cameras of an unspecified type ( n = 10) for photo‐taking. Other methods included smartphones (Brown, 2016; Holliday et al, 2018; Spiegel et al, 2020), a GPS with camera capabilities (Isogai et al, 2015), GoPros (Ahmed et al, 2022, 2023), or a tablet shared between all participants (Kahn‐John et al, 2020). Six studies did not specify the photo‐taking method used.…”
Section: Resultsmentioning
confidence: 99%
“…In 2011, Two-Eyed Seeing was adopted to guide the vision and mandate of the Canadian Institutes for Health Research and the Institute for Aboriginal Peoples' Health (CIHR, 2015). There has been an increase in the use of Two-Eyed Seeing to guide environmental sciences (Ahmed et al, 2022(Ahmed et al, , 2023Leonard et al, 2022), program development (Dunn et al, 2022;Marsh et al, 2022;Nicholson et al, 2021), education (Acharibasam & McVittie, 2022;Heuckmann & Zeyer, 2022), social justice (Cullen & Castleden, 2022), and discussions for cultural competency (Chatwood et al, 2015;Wright et al, 2019b). Moreover, there remains variation in how Two-Eyed Seeing is applied within the literature.…”
Section: Introductionmentioning
confidence: 99%
“…This is one of the factors contributing to the high rates of obesity, diabetes, heart disease and overall poorer physical and mental health [ 10 , 16 , 17 ]. Some studies have attributed this shift to climate change [ 10 ], and economic and social factors [ 18 , 19 ] such as the loss of language as a result of the residential school system [ 20 ]. The decline in the use of the Cree language has far-reaching implications, affecting social relationships, connections to the land, food security, land use, and economic development [ 18–20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Discussions with FAFN leadership and community members have highlighted the need for more on-the-land programs aligned with the seasonal harvesting practices of the Omushkego Cree. Previous initiatives, such as the Amisk (beaver) [ 18 ] and the Niska (goose) [ 19 ] harvesting programs, were harmonised with the seasons and were shown to revitalise cultural practices, facilitate healing from intergenerational trauma, and provide opportunities for knowledge dissemination from Indigenous perspective. The Sibi (river) program was the next harvesting program that followed the Omushkego Cree seasonal cycle and focused on fishing activities along the Albany River system.…”
Section: Introductionmentioning
confidence: 99%